Changes in lychee (Litchi chinensis Sonn.) texture and volatile compounds due to ultra-high pressure processing - C. Phanchaisri (2018)
© All Rights Reserved. The purpose of this study was to determine the changes of textural properties and flavor profiles of lychee after high pressure processing. It was found that the firmness values of pressurized lychee decreased with increasing pressure levels, temperatures and processing times, in particular lychee pressurized at 600 MPa and 60°C for 20 min. Considering the confocal scanning laser microscopic (CSLM) images, the microstructure of lychee treated under extreme conditions (600 MPa/60°C/20 min) was more severely affected than samples treated at 200 MPa and 20°C for 10 min. GC-MS chromatograms elucidated that ethanol and ethyl acetate were the major volatiles in fresh and pressurized samples. Pressurization at 200 MPa could maintain ester volatiles (freshness or fruity aromas) present in lychee better than more extreme processing level.